2022
DOI: 10.3346/jkms.2022.37.e147
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Late-Preterm and Term Infants Born to SARS-CoV-2-Positive Mothers

Abstract: With the spread of coronavirus disease 2019 (COVID-19) in Korea, the number of pregnant women infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is rapidly increasing. A shortage of negative-pressure isolation rooms for newborns makes hospital assignment more difficult for late-pregnant women with COVID-19. Among 34 infants born to SARS-CoV-2-positive mothers, 5 (14.7%) presented with respiratory distress and 1 (2.9%) presented with feeding intolerance that required specialized care. Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the early period of the pandemic, specifically between January, 2020 and February, 2021, the prevalence of COVID-19 in pregnant women was lower (0.02%) than in nonpregnant women in reproductive age (0.14%) [17,18]. Furthermore, the disease severity in pregnant women was not significantly higher than in the general population [17,[19][20][21].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the early period of the pandemic, specifically between January, 2020 and February, 2021, the prevalence of COVID-19 in pregnant women was lower (0.02%) than in nonpregnant women in reproductive age (0.14%) [17,18]. Furthermore, the disease severity in pregnant women was not significantly higher than in the general population [17,[19][20][21].…”
Section: Discussionmentioning
confidence: 92%
“…Since the first case of coronavirus disease (COVID- 19) was identified in December, 2019, many investigations have been conducted to determine whether this new infectious disease is related to maternal and fetal complications in pregnant women [1][2][3][4]. Maternal adaptation to pregnancy involves diverse anatomical and physiological changes, and in particular, immunological tolerance may increase maternal vulnerability to infectious diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported adverse neonatal outcomes of COVID-19 infected mothers; however, these associations are still unclear [ 7 , 8 , 12 ]. Currently, limited data with small sample sizes are available regarding the risk of perinatal infection and neonatal outcomes of infants born to COVID-19 infected mothers in Korea [ 1 , 13 , 14 ]. A recent Korean National Mother-Child Cohort study on neonatal outcomes discovered a possible association of COVID-19 mothers with increased NICU admission [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8,12) Currently, limited data with small sample sizes are available regarding the risk of perinatal infection and neonatal outcomes of infants born to COVID-19 infected mothers in Korea. 1,13,14) A recent Korean National Mother-Child Cohort study on neonatal outcomes discovered a possible association of COVID-19 mothers with increased NICU admission. 15) However, this association is not clear since the isolation policy may have affected admission.…”
Section: Introductionmentioning
confidence: 99%